2013
DOI: 10.4236/opj.2013.38a001
|View full text |Cite
|
Sign up to set email alerts
|

First Order Phase Transitions as Radiation Processes

Abstract: This paper presents new experimental evidence of the PeTa effect-infrared characteristic radiation under first order phase transitions, especially the crystallization of melts and the deposition and condensation of vapours/gases. The PeTa effect describes the transient radiation that a particle (i.e., atom, molecule or/and cluster) emits transient radiation during a transition from a meta-stable higher energetic level (in a super-cooled melt or a super-saturated vapour) to the stable condensed lower level (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In this paper, which is a sequel of the previous paper [23], we investigate certain peculiarities of PeTa radiation, and demonstrate the presence of PeTa energy sources in the atmospheres of Earth and Jupiter.…”
Section: In Our Experiments [23] the Increase Of Integral Radiation mentioning
confidence: 92%
See 2 more Smart Citations
“…In this paper, which is a sequel of the previous paper [23], we investigate certain peculiarities of PeTa radiation, and demonstrate the presence of PeTa energy sources in the atmospheres of Earth and Jupiter.…”
Section: In Our Experiments [23] the Increase Of Integral Radiation mentioning
confidence: 92%
“…This paper is the second paper of a set. In the first paper [23], a striking demonstration of the PeTa effect is presented. The paper describes the presence of infrared radiation during the deposition and condensation of air components at the temperature of liquid nitrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integral intensity of the radiation immediately decreased ( Figure 6, the time between points A1 and B1) as a result of the temperature decreasing to 77 K. Ice (evidently H 2 O and most likely CO 2 ) appeared on the cup surface and the integral intensity of the radiation increased ( Figure 6, the range between points B1 and C1). In the paper [37], it was shown that this is the PeTa radiation. While liquid nitrogen is inside the radiating cup, the intensity of the radiation is conserved ( Figure 6, the range between points C1 and D1).…”
Section: Peta Radiation At Different Temperaturesmentioning
confidence: 95%
“…In this section, we examine some experimental data concerning the influence of the temperature of the environment on the intensity of the PeTa radiation [37] [38] [39]. Of course, the scheme of the experiment does not correspond to the CL/SL/LIBL, but the experiment shows that the intensity of the PeTa radiation can increase with decreasing temperature of the environment.…”
Section: Peta Radiation At Different Temperaturesmentioning
confidence: 99%